Kontrol Sosial Pengasuh dalam Mencegah Bullying Pada Anak - Lestari, Endang (STKIP PGRI Ponorogo Press, 2024)
The aim of this research is to find out how caregivers’ social control prevents bullying behavior at Al-Fattah Al-Quran Education Center (TPA), Singgahan Village, Kebonsari, Madiun. The method used in this research is descriptive qualitative, with a case study research model. This research involved 35 students, aged 6-14 years and 4 caregivers as the research subjects. Data were obtained from interviews and observations of learning and caring process at the Al-Fattah Al-Quran Education Center (TPA), regarding the social control of caregivers in preventing bullying in children. The results of the research show that the Al Fattah Al-Qur’an Education Center (TPA) caregivers carry out social control to prevent bullying by; (1) prioritizing educational patterns, (2) implementing inviting patterns, and (3) implementing coercive strategies. If this can be done at the Al-Fattah Al Quran Education Center (TPA) effectively, bullying behavior will be minimized and prevented.